OPTIMIZING AND STRENGTHENING PHARMACOVIGILANCE TO ENSURE DRUG SAFETY IN PATIENTS’ CARE AT BAPTIST HOSPITAL MUTENGENE. - Bame , Julius; Nalubega, Jane Frank; Akankwasa, Edith; Okello, Elizabeth; Kavuma, David; Naggulu Posperia, Immaculate (Student's Journal of Health Research Africa, 2025)
In effective drug regulation systems, clinical practice, and public health programs, pharmacovigilance practice is of utmost importance (WHO, 2004). WHO defines Pharmacovigilance (PV) as “the science and activities related to the detection, assessment, understanding, and prevention of adverse drug effects or any other possible drug-related problems” (Beri et al., 2019; Hadi et al., 2017). Pharmacovigilance ensures the safety and efficacy of drugs throughout their life cycle. Following the evidence-based needs assessment (EBNA) of October 2022, high incidences of medication errors and adverse drug reactions were identified as the major concerns of pharmacovigilance in BHM, but recording was not done. Thus, a need for pharmacovigilance. This project aims to prevent or reduce the harm caused to patients by medication errors and ADRs by improving the knowledge of healthcare workers and the provision of a policy to enforce the practice of pharmacovigilance. Factors influencing the management of change are explored. They are divided into patient-related factors and health system-related factors. The change management models used to implement the change project are Lewin’s change theory, the I provisional change model, and the ADKAR Model. Influential persons were contacted and departments that use drugs for patient care were selected, and the change project was implemented. An evaluation of the level of implementation was done. The results of the evaluation were different for different PV activities in the different departments. There was a positive change in some activities; meanwhile, there was no improvement in some activities. Successful implementation of this project will go a long way to reduce or prevent some drug-related problems that cause treatment failure, harm, long hospitalization, increased cost of care, and death.